FoMO (Fear of Missing Out) pada Mahasiswa Pengguna Instagram di Kota Bandung - Nafalia Nurina Pratiwi; Umar Yusuf Supriatna (UNISBA Press, 2024)
Abstract. Social media is one of the media for the development of increasingly modern technology. The many features can make it easier for individuals to communicate, find out interesting activities or experiences carried out by others. However, in addition, excessive use of social media can cause FoMO. Fear of missing out (FoMO) is the worry or fear of missing out on valuable moments carried out by others where the individual cannot be present. To minimize this, individuals need to have self-control skills, one of which is patience. Patience is the ability to organize, control, direct (thoughts, feelings, and actions) in overcoming problems. This study aims to examine the effect of patience on fear of missing out (FoMO) on Instagram user students in Bandung City. This study uses a quantitative approach with a non-experimental causality design and multiple regression analysis techniques. The measuring instruments used were patience by Yusuf, U. (2021) and the Fear of Missing Out Scale developed by Przybylski, et al. (2013) and adapted by Azmi (2019). The results showed that there was a significant and negative effect of patience of 53.8% on the fear of missing out (FoMO) on Instagram user students in Bandung City and the most influential aspect of patience was the steadfast aspect. Abstrak. Media sosial menjadi salah satu media perkembangan teknologi yang semakin modern. Banyaknya fitur dapat memudahkan individu untuk berkomunikasi, mengetahui aktivitas atau pengalaman menarik yang dilakukan oleh orang lain. Namun, disamping itu penggunaan media sosial yang berlebihan dapat menyebabkan timbulnya FoMO. Fear of missing out (FoMO) adalah kekhawatiran atau ketakutan akan kehilangan momen berharga yang dilakukan oleh orang lain dimana individu tersebut tidak dapat hadir didalamnya. Untuk meminimalisir hal itu, individu perlu memiliki kemampuan pengendalian diri salah satunya kesabaran. Kesabaran adalah kemampuan untuk mengatur, mengendalikan, mengarahkan (pikiran, perasaan, dan tindakan) dalam mengatasi permasalahan. Penelitian ini bertujuan untuk menguji pengaruh kesabaran terhadap fear of missing out (FoMO) pada mahasiswa pengguna Instagram di Kota Bandung. Penelitian ini menggunakan pendekatan kuantitatif dengan desain kausalitas non-eksperimen dan teknik analisis regresi berganda. Alat ukur yang digunakan adalah kesabaran oleh Yusuf, U. (2021) dan Fear of Missing Out Scale yang dikembangkan oleh Przybylski, et al. (2013) serta diadaptasi oleh Azmi (2019). Hasil penelitian menunjukkan bahwa terdapat pengaruh dari kesabaran yang signifikan dan negatif sebesaar 53.8% terhadap fear of missing out (FoMO) pada mahasiswa pengguna Instagram di Kota Bandung dan aspek kesabaran yang paling berpengaruh yaitu aspek tabah.